2012
DOI: 10.4238/2012.august.24.9
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of the medicinal plant Maytenus robusta in mammalian cells in vivo

Abstract: ABSTRACT. Plants belonging to the Celastraceae family have been used in traditional medicine for their analgesic, anti-inflammatory and anti-ulcerogenic properties, among others. Maytenus ilicifolia is the principal species of this family, and is used in the treatment of gastric ulcers. However, owing to its inadequate management in Brazil, the species is becoming extinct and is being substituted with Maytenus robusta, which also displays gastroprotective activity. The aim of this study was to evaluate the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Also, the oral administration of hydroalcoholic extract from Maytenus robusta (Celasteraceae) over 7 days twice a day at dose of 10 mg/kg, in rats, did not produce any sign of toxicity [ 49 ]. However, in a previous study, the same plant extract indicated in vivo genotoxicity in mammalian cells at higher doses (250 or 500 mg/kg), while there was no genotoxic effect at 50 mg/kg [ 188 ]. Aqueous and chloroform extracts of Bauhinia purpurea (Fabaceae) [ 184 , 189 ] and ethanol extract of Parkia speciosa (Fabaceae) [ 62 ] at the single oral dose of 5000 mg/kg did not produce any sign of toxicity, behavioral abnormality or mortality in rats for the next 14 days, while its antiulcer activity was confirmed in all used in vivo models of gastric ulcer.…”
Section: Safety Of Plant Products Used As Antiulcerogenic Agentsmentioning
confidence: 99%
“…Also, the oral administration of hydroalcoholic extract from Maytenus robusta (Celasteraceae) over 7 days twice a day at dose of 10 mg/kg, in rats, did not produce any sign of toxicity [ 49 ]. However, in a previous study, the same plant extract indicated in vivo genotoxicity in mammalian cells at higher doses (250 or 500 mg/kg), while there was no genotoxic effect at 50 mg/kg [ 188 ]. Aqueous and chloroform extracts of Bauhinia purpurea (Fabaceae) [ 184 , 189 ] and ethanol extract of Parkia speciosa (Fabaceae) [ 62 ] at the single oral dose of 5000 mg/kg did not produce any sign of toxicity, behavioral abnormality or mortality in rats for the next 14 days, while its antiulcer activity was confirmed in all used in vivo models of gastric ulcer.…”
Section: Safety Of Plant Products Used As Antiulcerogenic Agentsmentioning
confidence: 99%
“…Some species of the genus Maytenus have been the object of toxicological evaluation, for example , Maytenus heterophylla senegalensis (da Silva et al ., ) or genotoxicity as with Maytenus robusta (Raymundo et al ., ). Niero et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some species of the genus Maytenus have been the object of toxicological evaluation, for example, Maytenus heterophylla senegalensis (da Silva et al, 2011) or genotoxicity as with Maytenus robusta (Raymundo et al, 2012). Niero et al (2011), a review of studies of the Maytenus genus, highlighted M. ilicifolia as the most studied species, with numerous studies on its potential antiulcerogenic properties, either as a crude extract or as a fraction or even as an isolated component, making this of great interest as a medicinal plant.…”
Section: Discussionmentioning
confidence: 99%
“…7 Other species of genus Maytenus, for example M. aquifolium, M. robusta and M. obtusifolia MART have shown antiulcer activity. [8][9][10] In Maytenus ilicifolia, acute diuretic activity and hipotensive activity were found, 11 as well as antiprotozoal activity which was attributed to quinonemethide triterpenes. 12 Furthermore, particular effects upon thecentral nervous system have been registered.M.…”
Section: Introductionmentioning
confidence: 99%